Informatization of linguistic education: personal mediatheque - O V Lvova (RUDN Journal of Informatization in Education, 2010)
A new innovational ICT tool - personal mediatheque - is offered and described in the article. Based on realization of the personal and activity-based approach it allows to solve a number of problems in increasing informational competence of a teacher as well as of a pupil.